Social Media as a Tool for Improving Writing Skills and Vocabulary: A Case Study on 8th Graders at SMP WR Supratman 1 Medan - Cynthia; Merry Kristian Ndruru (EduInovasi: Journal of Basic Educational Studies, 2025)
Referring to connectivism theory, it is understood that knowledge is distributed across a network where connections facilitate the dissemination of information. In this context, students are seen as actively engaged in creating their own networks, leading to the development of new, beneficial understanding. The study examines the unique contributions of each social media platform in improving students' writing and vocabulary skills. This research adopts a qualitative approach with interview and observation. The findings show that the use of social media such as Instagram, YouTube, and TikTok can improve writing skills and English vocabulary mastery among 8th grade students of SMP WR Supratman 1 Medan. Through the various types of content they access, students can practice writing in English in informal and formal contexts, which allows them to develop better writing skills. Although there are variations in how students use social media, all students showed improvements in their writing skills, especially in terms of sentence structure and the use of more varied vocabulary.